ANALYSIS FUZZY AHP FOR OPTIMIZATION CONTRACTOR SELECTION USING MULTI-CRITERIA IN DETERMINING THE BEST ALTERNATIVE CONTRACTOR - Rustandi, Dedi; Shilul Imaroh, Tukas (Dinasti International Journal of Management Science, 2021)
Using inappropriate criteria in contractor’s selection can lead to the failure of a construction project. This study aims to provide an optimal solution for contractor selection using multi-criteria. The criteria were obtained from previous research and concluded in the Focus Group Discussion. The analytical method used is Fuzzy-AHP, involving 14 experts who are registered contractors in the Company who have good performance and the contractor selection process involves a Tender Committee consisting of 5 appointed employees. The conclusion of this study shows that the criteria and weights that can be used for contractor selection are 35% bid, 22% technical ability, 13% financial ability, 11% reputation, 10% management ability and the last safety management with a weight of 9%. Each criterion has sub-criteria indicators with a total of 41 sub-criteria. Result of the consistency ratio below 10%. The conclusion contractor selection analysis using multi-criteria can screen the best contractor.